A review of Smart Grid Technology, Components, and Implementation - Yee Chong A.T.; Mahmoud M.A.; Lim F.-C.; Kasim H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Coal industry; Deforestation; Digital storage; Electric power transmission networks; Energy efficiency; Energy utilization; Fossil fuel power plants; Fossil fuels; Gas emissions; Global warming; Greenhouse gases; Microgrids; Sea ice; Sea level; Electrical energy; Electricity networks; Electricity transmission; Environmental destruction; Natural ecosystem; Renewable energies; Safety and efficiencies; Smart Grid technologies; Smart power grids